Analisis Kualitas Udara dalam Ruang dengan Gangguan Fungsi Paru pada Siswa MAN 1 Aceh Besar - Tiara Mairani; Agustina Agustina; Naimah Naimah; Wardiati Wardiati; Phossy Vionica Ramadhana (Yayasan Literasi Sains Indonesia, 2026)
Indoor air pollution in schools often shows high PM2.5 concentrations, primarily due to outdoor air infiltration and dust suspended by student activities. This study aims to analyze the relationship between indoor air quality and lung function impairment among students at MAN 1 Aceh Besar, located in an area with high vehicle density. Using a descriptive-analytical design with a cross-sectional approach, the study involved 78 students selected through proportional random sampling. Results showed that 17.9% of students experienced lung function impairment. PM2.5 concentrations in 65.4% of classrooms were found to exceed the threshold limit value (TLV) of 25 µg/m³, although statistically, it did not show a significant relationship with lung function impairment (p=0.07). However, students in rooms with high PM2.5 levels were 3.8 times more likely to experience impairment compared to those in rooms with PM2.5 levels below the TLV. Physical factors such as temperature (74.4% abnormal) and humidity (50% abnormal) also showed no statistically significant relationship with the students' lung function. Conversely, a significant relationship was found between smoking habits and lung function impairment (p=0.008), where students who smoke are 4.8 times more likely to experience lung function impairment. In conclusion, smoking habits are a risk factor that can increase PM2.5 concentration, damage the respiratory tract, and trigger lung function impairment in students.